Contact and Adoption Plans for Children Adopted from Out-of-home Care in New South Wales. Issue 4 (2nd October 2019) - Luu, Betty; Wright, Amy Conley; Cashmore, Judith
ABSTRACT: In New South Wales (NSW), legislation prioritises open adoption over long-term foster care when restoration is not possible, and suitable kin or guardians cannot be found. The adoption application includes an adoption plan that outlines the nature of a child's post-adoption contact with his or her birth family. There are efforts to include the views of the child, birth family, and prospective adoptive parents when developing this plan. This paper reports on the analysis of 89 adoption court files for 117 children from out-of-home care, finalised in 2017 by the Supreme Court of NSW. It focuses on the views of birth parents with respect to contact arrangements specified in the adoption plan. Three researchers independently coded the data, using an inductive approach based on grounded theory. The findings highlight the complexities in the changing relationship structures associated with adoption. Patterns of contact prior to adoption proceedings are highly predictive of plans for post-adoption contact. There are implications for social workers supporting positive contact experiences for children prior to an adoption order as well as the relationships between children's prospective adoptive families and birth families. IMPLICATIONS: Post-adoption contact decisions are informed by the views of birth family, children, and prospective adoptive parents, as well as the contact that has occurred pre-adoption. Birth parents expressed preferences for a specific amount and type of experience for contact, reflective of their relationships with the adoptive parents. Supports are needed to ensure that positive contact for children and relationships between children's birth family and adoptive family are established and maintained.